2016
DOI: 10.4236/msa.2016.79047
|View full text |Cite
|
Sign up to set email alerts
|

A Study by <i>Ab-Initio</i> Calculation of Structural and Electronic Properties of Semiconductor Nanostructures Based on ZnSe

Abstract: Our calculations are based on the modeling technique and simulation ab-initio that appeals to the Density Functional Theory (DFT) relying on the Full-Potential Linearized Augmented Plane Waves (FP-LAPW) method that requires a calculation process using approximations such as Local Density (LDA) and Generalized Gradient (GGA) developed in the modelling software of nanostructures WIEN2k. The optimal structure of the binary semiconductor ZnSe crystallizing in the complex phase of Zinc Blende (B3) was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The optimized structural parameters are a = 4.80 Å and c = 3.18 Å for bulk ZnF 2 into PBE calculations, in good agreement with the experimental values . In addition, our results of lattice constants are also in very good agreement with previous theoretical works. , …”
Section: Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The optimized structural parameters are a = 4.80 Å and c = 3.18 Å for bulk ZnF 2 into PBE calculations, in good agreement with the experimental values . In addition, our results of lattice constants are also in very good agreement with previous theoretical works. , …”
Section: Results and Discussionsupporting
confidence: 89%
“…39 In addition, our results of lattice constants are also in very good agreement with previous theoretical works. 40,41 Using the hybrid HSE functional, we improved the lattice parameter constants, in the sense that we have reduced (in modulus) the percentage of error with respect to the experimental data. Our findings with PBE + U calculations yield an underestimation of ZnO, ZnS, ZnS, and ZnF 2 lattice parameters (see Table 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The lattice constant parameters are reported in Table 1, with both PBE and PBE+U approximations, for ZnO hexagonal wurtzite (w-ZnO) and ZnX (X = S, Se or Te) cubic zinc blende bulk systems, and are compared with the experimental 39,40 and theoretical 41,42 values reported in the literature. It is shown that for all studied compounds the theoretical description, using the PBE functional, overestimates the lattice parameters for wurtzite and underestimates the lattice parameters for zinc blende in different percentages in comparison with the experimental data.…”
Section: Geometry and Structural Optimizationmentioning
confidence: 99%
“…an error change from 0.18 to 0.52% for bulk systems, in good agreement with other theoretical results. 41,42…”
Section: Geometry and Structural Optimizationmentioning
confidence: 99%